2022
DOI: 10.1108/jbsed-12-2021-0173
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of foreign direct investment: new evidence from West African regions

Abstract: PurposeThis paper aims to empirically investigate the factors attracting foreign direct investment (FDI) inflows into emerging economies.Design/methodology/approachThis study uses secondary data from the World Bank and the Global State of Democracy Indices of 16 West African countries (WACs) over the period from 1989 to 2018. Fixed- and random-effects econometric regression models are used to assess the nexus between 12 macroeconomic indicators (including political risk and cultural factors) and FDI inflows in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…Another recent study conducted by [ 33 ] examines the indicators of FDI for West African regions for the period of 1989–2018. In this study, fixed effect model (FEM) and random effect model (REM) were used to estimate the findings.…”
Section: Literature Review and Hypotheses Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another recent study conducted by [ 33 ] examines the indicators of FDI for West African regions for the period of 1989–2018. In this study, fixed effect model (FEM) and random effect model (REM) were used to estimate the findings.…”
Section: Literature Review and Hypotheses Formulationmentioning
confidence: 99%
“…Most of the previous studies confirmed that the relationship between GDP growth and FDI is significant and positive. In recent times, many studies investigated it and found a positive relationship between GDP growth and FDI, and they include studies by [ 40 ] on MENA countires, [ 34 ] on highly emerging BRICS countries, [ 37 ] on China, [ 42 ] on 124 countires, [ 1 ] on Europe, [ 33 ] on West African regions, [ 46 ] on OECD countries, [ 6 ] on Brazil, [ 47 ] on China, [ 7 ] on Caribbean countries, [ 48 ] on China, [ 49 ] on 15 countries, [ 50 ] on 189 countries, [ 51 ] on Greece, [ 52 ] on 151 countries, and [ 53 ] on China and ASEAN countries. On the other hand, a few studies noted that higher GDP levels reduce FDI significantly, and they include studies by [ 54 ] on BRIC countries (Brazil, Russia, India and China) and CIVETS (Colombia, Indonesia, Vietnam, Egypt, Turkey and South Africa) countries, [ 55 ] on G20 countries, and [ 56 ] on 33 countries.…”
Section: Literature Review and Hypotheses Formulationmentioning
confidence: 99%
“…Dewi dan Hutomo (2021) juga berpendapat bahwa market size yang tinggi menggambarkan pertumbuhan ekonomi suatu daerah yang baik sehingga menarik FDI. Adapun penelitian yang lain juga menemukan pengaruh positif market size terhadap FDI yaitu penelitian yang dilakukan oleh Fu et al (2018), Korsah et al (2022), Chandra dan Handoyo (2022), Awad (2020), serta Saad dan Lukman (2020). H2: Labor force berpengaruh positif terhadap FDI Hasil uji hipotesis menunjukkan variabel labor force memiliki nilai t statictic 4,515 dan nilai signifikansi 0,000.…”
Section: Uji Koefisien Determinasiunclassified
“…One of the concerns of policymakers is identifying the drivers of investment required to spur economic growth. Some scholars have examined the drivers of either foreign direct investment (FDI) or domestic investment (Anyanwu, 2012; Anyanwu & Yameogo, 2015; Bosire, 2019; Korsah et al, 2022; Matthew et al, 2021; Mlambo, 2001; Njuguna & Nnadozie, 2022; Ogbeide & Adeboje, 2020; Okafor et al, 2017; Sekkat & Veganzones‐Varoudakis, 2007). These include infrastructure such as the quality of electricity, telecommunication and roads (Anyanwu, 2012), business environment or investment climate and market policies (Matthew et al, 2021; Sekkat & Veganzones‐Varoudakis, 2007), among others.…”
Section: Introductionmentioning
confidence: 99%